Biodiversity of fish resources in Sungsang Estuaries of South Sumatra. (May 2019) - Fauziyah,; Nurhayati,; Bernas, S M; Putera, A; Suteja, Y; Agustiani, F
Abstract: The purpose of this study was to assess the fish biodiversity of Sungsang estuaries in South Sumatra. The species diversity, evenness, dominance, degree of similarity, and composition of fish communities as well as some physicochemical conditions were analyzed in order to establish the baseline data inventory of Sungsang estuaries. The results show that all of the physico-chemical parameters were in good condition for fish sustainability. Forty-eight (48) species of fish belonging to 29 families of freshwater, brackish water and marine sources were encountered in the water bodies. Johnius belangerii, Johnius amblycephalus and Setipinna taty were species with a relatively high abundance, but the appearance frequency of these species was high, medium and low, respectively. The value of the Shannon's diversity index for fish resources was classified as moderate (H'=1.477-2.708). The index value of evenness was classified as high (J'= 0.616 – 0.876), while the index value of dominance was classified as low (D = 0.097 – 0.382). This result indicate that the species diversity was good enough, the species spread was evenly distributed, that there was a stable community structure and no domination.